Bilateral asymmetry of knee and ankle isokinetic torque in soccer players u20 category - Costa Silva, J. R. L.; Detanico, D.; Dal Pupo, J.; de la Rocha Freitas, C. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2015)
Bilateral asymmetries and muscle imbalances are associated with increased risk for lower limb injuries and still seem to imply in athletes performance. This study aimed to analyze bilateral asymmetry of soccer players in age category below 20 years old (peak torque and conventional and functional reason in extensor/flexors of knee and inverter/eversion of ankle) and to compare these variables between defending, midfield and attacker players. The study included 22 athletes in age category below 20, which underwent a five maximal isokinetic testing with repetitions at 180°/s for knee and 120°/s for ankle, both concentric and eccentric actions. T test for dependent data was used to compare values of torque between dominant and non-dominant limbs and one-way ANOVA was used to compare neuromuscular variables between players of different positions, both at p <0.05. No significant differences were observed in any neuromuscular variable (peak torque and functional and conventional ratio) between dominant and non-dominant sides (p> 0.05). It was found that defensive players had eccentric torque values of extensors knee higher than midfield players (p <0.05). Defensive players exhibit greater eccentric torque of knee extensor muscles compared to midfield players. It can be concluded that the analyzed soccer players did not present bilateral asymmetries in flexor/extensor knee muscles neither in inverter/eversion ankle muscles.